First They Came for the Physical Crips: The Eugenic Logic Driving MAID - Janz, Heidi (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
In this paper, I critically examine the expansion of Medical Assistance in Dying (MAiD) in Canada through a disability ethics lens. I argue that the dominant narrative framing MAiD as a compassionate, autonomy-enhancing policy obscures the systemic ableism embedded in its implementation. Drawing on lived experiences, legal decisions, and bioethical debates, I demonstrate how disabled individuals are increasingly driven to seek MAiD not due to their medical conditions, but because of structural neglect, poverty, and lack of support. I critique the “harm reduction” justification for MAiD, showing that it perpetuates a eugenic logic that devalues disabled lives. By foregrounding disability ethics, I propose a redefinition of autonomy that recognises interdependence and challenges the biomedical privileging of individualism. This approach exposes the ethical flaws in current MAiD policy and calls for a shift toward anti-ableist, disability-affirming practices in healthcare and bioethics. Ultimately, I argue that without such a shift, MAiD risks becoming a path of least resistance for structurally vulnerable disabled people, rather than a truly autonomous choice.